Efeitos da administração de eritropoietina na dislipidemia e na hipertrofia ventricular esquerda de camundongos hiperlipidêmicos - Rosa, Bruno Barbosa; Terra, Gerusa Dias Siqueira Vilela; Garcia, José Antonio Dias; Neiva, Cassiano Merussi [UNESP] (My University, 2014)
The main purpose of this work was to evaluate the effects of erythropoietin (EPO) on the lipid profile and in left ventricular hypertrophy (LVH) in mice LDLr-/-, fed a high fat diet. Were used twenty-four mice LDLr- / -, male, 3 months old, proportionally divided in 3 groups: S Group, fed with standard diet; HL Group, fed with high fat diet (20% fat total and 1.25% cholesterol, 0.5% cholic acid); HL + EPO Group, fed with high-fat diet and treated with EPO on weekly dose of 200UIkg, subcutaneously. After 75 days of experiment the development of LVH, serum concentrations of glucose, triglycerides (TG), total cholesterol (TC), and low, very low and high density lipoprotein (LDL, VLDL and HDL, respectively) in addition to the left ventricular mass ratio and the total mass of the animal (ventricular mass(mg)/total animal mass(g)) were evaluated. The experimental protocol was approved by the University Ethics Committee of the Experimental Studies under the number 13A/2010. At the end of the trial period, the mice of the HL presented development of LVH with increase in serum concentrations of CT, LDL, VLDL, TG and glucose and a decreased of HDL concentrations, when compared with parameters of mice of the Group S. The use of EPO by HL+EPO group increased serum concentrations of HDL, compared with the HL group (p<0,05) and prevented LVH. In addition, reduced the serum concentrations of TC, LDL, and glucose (p<0,05). However, EPO was not efficient in preventing the hypertriglyceridemia and still, wasn’t able to reduce VLDL concentrations induced by the diet HL. In conclusion, the EPO presented some cardio protective effects, preventing the HVE as well as correcting some of the biochemical variables diet HL-induced. These effects may be, in part, related to increased plasma concentrations of HDL.

O principal objetivo deste trabalho foi avaliar os efeitos da eritropoietina (EPO) no perfil lipídico e na hipertrofia ventricular esquerda (HVE) de camundongos LDLr- /- alimentados com dieta hiperlipídica. Foram utilizados vinte e quatro camundongos LDLr-/-, machos, 3 meses de idade, equinumericamente divididos em 3 grupos: Grupo S, alimentados com dieta padrão; Grupo HL, alimentados com dieta hiperlipídica (20% de gordura total e 1,25% de colesterol, 0,5 % ácido cólico); Grupo HL+EPO, alimentados com dieta hiperlipídica e tratados com EPO na dose semanal de 200UI/kg via subcutânea. Após 75 dias de experimento foram avaliadas a desenvoltura da HVE e as concentrações séricas de glicose, triglicérides (TG), colesterol total (CT) e de lipoproteínas de baixa densidade (LDL), de muita baixa densidade (VLDL), e de alta densidade (HDL) além da razão entre a massa ventricular esquerda e a massa total do animal: massa ventricular (mg)/ massa do animal(g). O protocolo experimental foi aprovado pelo Comitê de Ética Experimental da Universidade sob o número 13A/2010. Ao final do período experimental, os camundongos do grupo HL apresentaram desenvolvimento de HVE com aumento nas concentrações séricas de CT, LDL, VLDL, TG e glicose e redução do HDL, quando comparados com parâmetros dos camundongos do grupo S. O uso da EPO pelo grupo HL+EPO aumentou significativamente (p<0,05) as concentrações séricas do HDL, quando comparados com o grupo HL, e preveniu a HVE. Além disso, reduziu as concentrações de CT, LDL e glicose (p<0,05). Entretanto, a EPO não foi eficiente em impedir a hipertrigliceridemia e tão pouco foi capaz de reduzir as concentrações de VLDL induzidas pela dieta HL. Em conclusão, a EPO apresentou alguns efeitos cardioprotetores, prevenindo a HVE bem como corrigindo algumas das variáveis bioquímicas induzidas pela dieta HL. Estes efeitos podem estar em parte, relacionados ao aumento das concentrações plasmáticas de HDL.
Effects of administration of the erythropoietin in dyslipidemia and left ventricular hypertrophy of hyperlipidemic mice
Keywords: Dislipidemy; Left ventricular hypertrophy; Erythropoietin; Mice LDLr-/-; Dislipidemia; Hipertrofia ventricular esquerda; Eritropoietina; Camundongos LDLr-/-